Evaluation of liquefaction resistance in chemically grouted sand using cyclic triaxial tests - Khin Nyein Chan Kyaw; Toshiyuki Motohashi; Shigeo Sasahara; Shinya Inazumi (Results in Engineering)
Liquefaction induced by earthquakes poses a significant threat to infrastructure, particularly in loose sandy soils. Chemical grouting is a widely used countermeasure to enhance soil stability; however, its effectiveness under dynamic loading lacks standardized quantitative evaluation methods. This study evaluates the liquefaction resistance of chemically grouted sand using stress-controlled and strain-controlled cyclic triaxial tests. Specimens treated with colloidal silica at concentrations of 6 %, 8 %, and 10 % were tested under undrained conditions with an effective confining pressure of 100 kPa and a loading frequency of 0.1 Hz. The strain-controlled method, applying a constant double-amplitude axial strain, was introduced as an alternative to mitigate tensile failure (necking) observed in stress-controlled tests. Liquefaction resistance was assessed using excess pore water pressure, axial strain criteria, and cumulative dissipated energy as a unified evaluation index. Results showed that higher silica concentrations significantly improved liquefaction resistance, with the 10 % concentration providing the greatest cyclic strength. Strain-controlled tests demonstrated greater consistency and avoided premature tensile failure, while cumulative dissipated energy correlated strongly with liquefaction resistance across both methods. These findings suggest that strain-controlled cyclic triaxial testing is a reliable alternative for evaluating liquefaction resistance in chemically treated soils and support its integration into performance-based geotechnical design frameworks.